Revisiting the Miles and Snow Typology: Strategic Path Mediates Business Strategy and Resource Configuration for Innovation - Zubaedah, Yasmina; Fontana, Avanti; Afiff, Adi Zakaria (UI Scholars Hub, 2013)
This article provides the results of an exploratory study that investigated the effect of Capability Lifecycle Path on attaining effective adaptation through innovation. Based on Miles and Snow (1978), an empirical study was conducted to explore whether performing firms are those that indicate consistency within the strategy, process, structure and Capability Lifecycle Path arrangement. The basic premise of this study is adaptability for sustainability, where firms go through adaptation cycles through Business Model Innovation would perform well when they are able to consistently create value and effectively manage adopted business models, or denoted as Business Model Effectiveness. Using data obtained from seven Indonesian firms in various industries, PLS Analysis was conducted to investigate the relationships between Business Strategy, Firm Resource Configuration, Capability Lifecycle Path and Business Model Effectiveness. Findings indicated that Capability Lifecycle Path, or decisions made on the development of capabilities at the mature stage, is an important part of the series of decisions made during adaptation to ensure performance.